Towards a catalog of conflicts for HCI quality characteristics in UbiComp and IoT applications: Process and first results - Carvalho, Rainara Maia; Andrade, Rossana M. C.; de Oliveira, Kathia Marcal (Proceedings of the ... International Conference on Research Challenges in Information Science, 2018)
Conflicts between non-functional requirements (NFRs) can happen when a particular solution favors the first NFR but creates difficulty for the second one. Usually, in the literature, the conflict identification uses catalogs to indicate conflicting NFRs. The authors focus on NFRs that are generic to any system. However, applications from Ubiquitous Computing (UbiComp) and Internet of Things (IoT) introduce new kind of NFRs (e.g., Context-Awareness and Mobility). They are not included in these catalogs and can impact the traditional ones (e.g., Security and Usability). Therefore, there is a need to create a catalog that considers conflicts among quality characteristics for UbiComp and IoT applications. However, the literature lacks a process or guideline about how to create a catalog. This paper aims then to present a process and initial findings towards a catalog of conflicts between specific HCI quality characteristics in UbiComp and IoT applications and Usability.